Evaluation of guidance and counselling services in enhancing sexually abused early childhood learners in Kinangop Sub-County, Nyandarua County, Kenya - Wambui Ndegwa, Mary; Edabu, Dr. Paul (IJRDO - Journal of Social Science and Humanities Research, 2016)
This study aimed to evaluate the applicability of guidance and counseling services for sexually abused early childhood learners in Kinangop Sub-county, Nyandarua County, Kenya. This study was guided by The Attachment Theory which was postulated by Bowlby (1990). The study adopted mixed methods approach and a descriptive survey. Target population comprised the 53 ECDE Center managers, 146 ECDE Teachers, 106 parents’ representatives, five Children’s officers and 1190 ECDE Children all totaling to 1500. The researcher sampled 20% of the targeted ECDE Centers, that is, ten ECDE Centers. Similarly, based on the same proportion, 20% of the target population, that is, 300 respondents were sampled. Stratified sampling was applied to create five strata based on the number of zones in Kinangop Sub-county. From each stratum, two ECDE Center managers and nine ECDE Teachers were selected using purposive sampling. The Children’s Officers were also selected using purposive sampling. Six parents’ representatives and 43 ECDE children were selected using simple random sampling. Qualitative data was analyzed based on research objectives while quantitative data was nalyzed using ANOVA in Statistical Packages for Social Science (SPSS Version 21). The study established that applicability of guidance and counseling amongst sexually abused  children has not been fully realized. The study thus recommends that ECDE Centers should start guidance and counseling units within the centers for sexually abused children to help mitigate against trauma and other attendant consequences of sexual abuse. Stakeholders should be trained on different child protection measures so that they can be able to identify and prevent cases or potential instances of child sexual abuse (CSA).